Rethinking India’s Nuclear Doctrine: Challenges and Opportunities in a Multipolar Asia - Rajesh, Aadi (Honvédségi Szemle – Hungarian Defence Review, 2025)
The nuclearization of Asia’s security architecture poses a significant challenge for countries across the continent and beyond. As China and India engage in a strategic competition for Asian dominance in the 21st century, the nuclear issue has become a critical policy and security challenge for both nuclear-armed rivals. China’s explosive economic and military growth has altered the balance of power in Asia, challenging the security assumptions and architectures of countries throughout the continent. While nations remain wary of Chinese dominance, India, China’s key competitor in Asia, remains focused on preventing a Chinese-dominated Asian security and economic architecture. However, due to a shift in the balance of power in China’s favour over the past three decades, India is developing strategies to reduce and mitigate the power asymmetry. Among these strategies are plans to amend its nuclear policies and explore new avenues for deterrence and offensive capabilities. The paper will compare the nuclear doctrines of India, China, and Pakistan, examining the gaps and challenges in India’s policy relative to its nuclear-armed neighbours. Additionally, it will explore how India is reimagining its nuclear policy and security strategies to counterbalance China.